Batata cv Pirassu como matéria prima industrial - Garcia, Emerson Loli [UNESP]; Leonel, Magali [UNESP]; Carmo, Ezequiel Lopes do; Pádua, Joaquim Gonçalves de [UNESP] (EIA Energy in Agriculture, 2014)
The starch market has been growing and improving in recent years, leading to a search for products with specific characteristics that meet the industrial requirements. This work aimed to evaluate the centesimal composition of potato tubers cv Pirassu and its industrial potential. The potato cv Pirassu was cultivated in Pouso Alegre, mountainous region south of Minas Gerais state, with planting season in August and harvest season in November, 2011. The tubers were analyzed for color, pulp and centesimal composition. The starch extract was analyzed for centesimal composition, phosphorus content, apparent amylose, pasting properties and thermal properties. The results showed that the content of dry matter, total soluble sugar and starch of tubers, are compatible for processing for potato chips. The starch of this cultivate showed important viscosity characteristics for food industry such as: heat resistance and friction, good final viscosity and low granular organization.

O mercado de amido vem crescendo e se aperfeiçoando nos últimos anos, levando a busca de produtos com características específicas que atendam as exigências industriais. neste trabalho objetivou-se avaliar a composição centesimal dos tubérculos da batata cv pirassu e suas potencialidades industriais. a batata cv pirassu foi cultivada no município de pouso alegre, região serrana ao sul de minas gerais, com plantio em agosto e colheita em novembro de 2011. os tubérculos foram analisados quanto à cor da casca, polpa e composição centesimal. o amido extraído foi analisado quanto à composição centesimal, teor de fósforo, amilose aparente, propriedades de pasta e propriedades térmicas. os resultados obtidos mostraram que os teores de matéria seca, açúcar solúvel total e amido dos tubérculos são compatíveis para o processamento na forma de fritas tipo chips. o amido apresentou características importantes de viscosidade, tais como: resistência ao calor e atrito, boa viscosidade final e fraca organização granular, características importantes para a indústria alimentícia.
Potato tubers cv pirassu as industrial raw materials
Keywords: Solanum tuberosum L.; Rheological properties; Starch; Solanum tuberosum L.; Propriedades reológicas; Amido